Perbandingan Aplikasi Rotor Tunggal dan Ganda terhadap Performa Turbin Air Tipe Propeller pada Saluran air Debit Rendah - Miftahul Ulum; Michael Azzura Akbar; M Arif; Saif Muizzadin Wadaullah (Institut Teknologi Adhi Tama Surabaya, 2022)
The propeller turbine is a water turbine that is suitable for use at low heads such as irrigation canals and rivers. Hydrokinetic energy development is the most feasible option in Indonesia. However, currently the development of hydrokinetic energy in Indonesia is still very low. The propeller turbine is a water turbine which is suitable for use at low heads. This turbine is classified as a microhyro and has a head between 1-5 m. This study was conducted to compare the effect of using a double rotor on a propeller turbine. Changes in turbine performance were reviewed through the rotational speed of the rotor, torque, mechanical power and turbine electrical voltage. This research was conducted experimentally in a closed-loop test section. A pump drives fluid flowing in the closed-loop test section at flow rates of 0.05, 0.1 and 0.15 liter/s. the use of a double propeller turbine results in an increase in turbine performance above 5%. This is because turbines with double rotors have a large cross-sectional area compared to single-rotor turbines. Thus the energy contained in the fluid can be transmitted optimally to drive the turbine surface with a double rotor.Keyword: Turbin Propeller, Double rotor, microhydro